Assessing species' vulnerability to climate change - Foden, Wendy Bernardina (My University, 2015)
Climate change (CC) is expected to have profound impacts on biodiversity, but predicting these remains a major scientific challenge. Current approaches to quantifying such impacts focus largely on measuring exposure to CC, ignoring the biological traits that may significantly increase or reduce species’ vulnerability. In addition, their input requirements restrict use to wide-spread and better-studied species, creating taxonomic and geographic biases in global CC vulnerability estimates. To address this, I developed a framework which draws on both biological traits and exposure modelling to assess three dimensions of CC, namely exposure, sensitivity and adaptive capacity. In the first fully-representative study of entire taxonomic groups, my collaborators and I applied this framework to each of the world’s birds, amphibians and corals (16,857 species). Results identify the Amazon as an area of high concentration of CC vulnerable birds and amphibians, and the central Indo-west Pacific (Coral Triangle) for corals. Comparisons with species’ IUCN Red List threat statuses reveal species and regions both of new and greatest overall priority for conservation globally.
A thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy. Johannesburg, 2014.
Keywords: Climatic changes.; Climatic changes--Biodiversity.; Climatic changes--Environmental aspects.